1982
DOI: 10.1002/1097-0142(19820415)49:8<1721::aid-cncr2820490832>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate analysis of the prognosis after surgical treatment of malignant soft-tissue tumors

Abstract: Ninety-seven patients who had received their primary and definitive surgical treatment for a soft-tissue sarcoma during the years 1956--1976 were studied with respect to local recurrence, metastasis, and survival. The aim of the treatment was to eradicate the tumor while preserving good function. The influence of host and tumor properties and different diagnostic and surgical procedures on the prognosis was studied by means of nonparametric multivariate analysis. Ninety-four percent of the tumors were located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
122
1
7

Year Published

1985
1985
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(145 citation statements)
references
References 25 publications
14
122
1
7
Order By: Relevance
“…histological grade, size, depth, degree of necrosis etc. (Trojani et al, 1984;Rooser et al, 1988;Ueda et al, 1988;Mandard et al, 1989) [ion or on various treatment modalities (Markhede et al, 1982;Bramwell et al, 1985;Suit et al, 1985). In addition, most of tl in sarcoma patients is difficult to assess reliably these observations have been made on hospital-based or on of the rarity of such tumours, their differing toposelected sub-sets of population-based series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…histological grade, size, depth, degree of necrosis etc. (Trojani et al, 1984;Rooser et al, 1988;Ueda et al, 1988;Mandard et al, 1989) [ion or on various treatment modalities (Markhede et al, 1982;Bramwell et al, 1985;Suit et al, 1985). In addition, most of tl in sarcoma patients is difficult to assess reliably these observations have been made on hospital-based or on of the rarity of such tumours, their differing toposelected sub-sets of population-based series.…”
Section: Resultsmentioning
confidence: 99%
“…Most published data on survival in sarcomas relates to selected patients referred to specialist treatment centres (Markhede et al, 1982;Bramwell et al, 1985;Collin et al, 1987;Stotter et al, 1990;El-Jabbour et al, 1990). Survival data from other, more broadly-based groups, have not relied upon centrally reviewed histological diagnoses for all the cases included (Tucker & Fraumeni, 1982;Fraumeni & Boice, 1982).…”
mentioning
confidence: 99%
“…Since then other authors (Mandard et al, 1989;Rooser et al, 1988;Trojani et al, 1984) have, like us, shown it to be an independent prognostic factor. Assessment of the extent of necrosis is the most subjective and difficult of the criteria used in grading (Costa et al, 1984;Trojani et al, 1984 (Mandard et al, 1989;Ueda et al, 1988) and site (Collin et al, 1987;Markhede et al, 1982) is well documented in the literature. In this study, size was an independent prognostic factor in the superficial STS but not in either the overall group or the deep STS.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 With regard to bone sarcomas, all osteosarcomas were high-grade malignant. Chondrosarcomas were graded in three grades and dedifferentiated.…”
Section: Microscopic Evaluation and Reporting Of Cnb And Surgical Excmentioning
confidence: 99%